(untitled) (Social Science Review, 2021)
Governments around the world are encouraging private individuals, groups or organizations to join hand in hand in delivering better services to the citizens. Similarly, Government of Bangladesh has also initiated Public Private Partnerships (PPP) in its policies and strategies over the years. Mayor Muhammad Hanif Flyover (MMHF) is one of the key examples of large-scale project implemented under PPP in the country. The main objective of this paper is to assess the level of satisfaction of the service users of MMHF and associated factors that either facilitate or hamper user satisfaction. This study follows a mixed research method with both quantitative and qualitative data collection techniques; small scale survey and interview applied to cover primary sources and content analysis has been applied to get information from secondary sources. This study customizes TCV (time, cost and visit) model used by a2i to assess the efficacy of the use of MMHF. This study finds that most of the service users are satisfied with the time needed to pass through the flyover against the costs incurred and thereby they happily avail the flyover. Despite some challenges this PPP project has paved the opportunity to introduce more partnerships between government and the private sector. Social Science Review, Vol. 37(2), Dec 2020 Page 43-57